Publishing - Živković, Daniela (2007)
The author carried out a research in the publishing activity of the National and University Library on the basis of its catalogue. She classified works by their types and series, when possible, and described different works pointing to their documenting the library activity.
Povodom svoje 400. obljetnice nacionalna i sveučilišna knjižnica je objavila dva usporedna izdanja spomenice, jedno na hrvatskom, a drugo na engleskom jeziku.
Projekt MZOS
ENG